The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40496-021-00295-5
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Clinical and Systemic Results of Periodontitis Treatment in Obese Individuals?

Abstract: Purpose of Review Periodontitis and obesity are characterized by a dysregulated inflammatory state. Obese individuals have a higher chance of presenting periodontitis. Clinical studies in different populations demonstrate that individuals with obesity have worse periodontal conditions. This current review aims to explore recent literature to understand what the impacts of obesity on periodontal treatment outcomes are and to learn whether periodontal treatment can improve systemic biomarkers in obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…Nevertheless, there remains controversy in the previous studies regarding the effect of PA on bone metabolism. Some studies suggest that PA exhibits high lipotoxicity and can negatively affect the osteogenic differentiation of osteoblasts, 18,33,54 while other studies suggest that PA affects bone homeostasis mainly by influencing osteoclasts rather than osteoblasts 48–50 . According to our present study supported by systematical observation, when exposed to PA, the osteogenic potential of PDLSCs was notably impaired (Figure 1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, there remains controversy in the previous studies regarding the effect of PA on bone metabolism. Some studies suggest that PA exhibits high lipotoxicity and can negatively affect the osteogenic differentiation of osteoblasts, 18,33,54 while other studies suggest that PA affects bone homeostasis mainly by influencing osteoclasts rather than osteoblasts 48–50 . According to our present study supported by systematical observation, when exposed to PA, the osteogenic potential of PDLSCs was notably impaired (Figure 1).…”
Section: Discussionsupporting
confidence: 76%
“…Increasing evidence has confirmed that obesity and obesity‐related complications are associated with the onset, progression and recovery of periodontitis 2,3,49,50 . However, the specific mechanism is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the increase in dietary carcinogenicity along with the increase in weight in a significant part of the society should alarm dental hygienists. All of the above factors significantly contribute to the increased risk of periodontal disease exacerbation as well as to its longer and more difficult treatment in the future [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, overweight/obese individuals are more likely to suffer from periodontitis compared to normal weight individuals in the control sample. 24 In general, obese individuals with periodontitis can significantly benefit from nonsurgical periodontal treatment, which reduces several biochemical biomarkers of obesity with or without weight loss 37 .…”
Section: Discussionmentioning
confidence: 99%